2019
DOI: 10.3892/mmr.2019.10034
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA‑1 downregulation induced by carvedilol protects cardiomyocytes against apoptosis by targeting heat shock protein 60

Abstract: Myocardial infarction (MI) is the most common event in cardiovascular disease. Carvedilol, a β-blocker with multiple pleiotropic actions, is widely used for the treatment cardiovascular diseases. However, the underlying mechanisms of carvedilol on alleviating MI are not fully understood. The aim of the present study was to investigate whether the beneficial effects of carvedilol were associated with regulation of microRNA-1 (miR-1). It was demonstrated that carvedilol ameliorated impaired cardiac function and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 40 publications
(47 reference statements)
2
18
0
Order By: Relevance
“…We found that treatment with co-enzyme Q10 alone did not influence the viability of myocardial cells, demonstrating that co-enzyme Q10 may be a safe drug to use to protect chickens from heat stress (Xu et al 2017a). Consistent with previous studies, we found that heat stress reduced the viability of primary chicken myocardial cells (Wang et al 2017;Hu et al 2019;Liu et al 2019); this reduced viability may be associated with the generation and accumulation of ROS that can result in increased oxidative damage (He et al 2019;Tiwari et al 2019). Pretreatment with co-enzyme Q10 significantly suppressed the decline in cell viability during heat stress, reduced cell apoptosis, and reduced ROS generation induced by heat stress.…”
Section: Discussionsupporting
confidence: 90%
“…We found that treatment with co-enzyme Q10 alone did not influence the viability of myocardial cells, demonstrating that co-enzyme Q10 may be a safe drug to use to protect chickens from heat stress (Xu et al 2017a). Consistent with previous studies, we found that heat stress reduced the viability of primary chicken myocardial cells (Wang et al 2017;Hu et al 2019;Liu et al 2019); this reduced viability may be associated with the generation and accumulation of ROS that can result in increased oxidative damage (He et al 2019;Tiwari et al 2019). Pretreatment with co-enzyme Q10 significantly suppressed the decline in cell viability during heat stress, reduced cell apoptosis, and reduced ROS generation induced by heat stress.…”
Section: Discussionsupporting
confidence: 90%
“…MiR-1 is deemed an important regulator in cardiac development and disease, more specifically, in the regulation of cardiomyocyte apoptosis in the latter. 186 They observed how miR-1…”
Section: F I G U R Ementioning
confidence: 99%
“…They observed how miR‐1 overexpression was associated with decreased cell viability and how the effect of carvedilol is to precisely counteract this result via downregulation of miR‐1 and thus exercising an antiapoptotic reaction 186 . In an effort to further analyze this mechanism, expression of HSP60 was measured, a target of miR‐1 186 . Carvedilol was able to increase mRNA expression levels of HSP60 while simultaneously downregulating miR‐1 expression 186 .…”
Section: Therapeutic Strategies Targeting the Hsp60 Signaling Pathwaymentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, administration of a miR-1 mimic to rats with left ventricular hypertrophy causes reversion of cardiac hypertrophy and alleviation of fibrosis and apoptosis which are recognized to be a major feature of cardiac remodeling and HF. Although a report by Hu et al is suggestive of downregulation of miR-1 by means of carvedilol in an animal model of myocardial infarction (MI), 59 it seems that miRNAs play different roles in different species as well as different physiological and pathological conditions. 46,47 Altogether, it can be postulated that miR-1 may reduce cardiac hypertrophy, 60 that mediates the protective effects of carvedilol or at least this inference deserves further studies to obtain supporting evidence.…”
Section: Dovepressmentioning
confidence: 99%